Effect of mode of intraoperative support on primary graft dysfunction after lung transplant - Loor, Gabriel; Huddleston, Stephen; Hartwig, Matthew; Bottiger, Brandi; Daoud, Daoud; Wei, Qi; Zhang, Qianzi; Ius, Fabio; Warnecke, Gregor; Villavicencio, Mauricio A.; Tirabassi, Briana; Machuca, Tiago Noguchi; et al. (The journal of thoracic and cardiovascular surgery, 2022)
Objective - To clarify the relationship between the use of extracorporeal life support during lung transplantation and severe primary graft dysfunction (PGD), we developed and analyzed a novel multicenter international registry. - Methods - The Extracorporeal Life Support in Lung Transplantation Registry includes double-lung transplants performed at 8 high-volume centers (>40/year). Multiorgan transplants were excluded. We defined severe PGD as grade 3 PGD (PGD3) observed 48 or 72 hours after reperfusion. Modes of support were no extracorporeal life support (off-pump), extracorporeal membrane oxygenation (ECMO), and cardiopulmonary bypass (CPB). To assess the association between mode of support and PGD3, we adjusted for demographic and intraoperative factors with a stepwise, mixed selection, multivariable regression model, ending with 10 covariates in the final model. - Results - We analyzed 852 transplants performed between January 2016 and March 2020: 422 (50%) off-pump, 273 (32%) ECMO, and 157 (18%) CPB cases. PGD3 rates at time point 48-72 were 12.1% (51 out of 422) for off-pump, 28.9% for ECMO (79 out of 273), and 42.7% (67 out of 157) for CPB. The adjusted model resulted in the following risk profile for PGD3: CPB versus ECMO odds ratio, 1.89 (95% CI, 1.05-3.41; P = .033), CPB versus off-pump odds ratio, 4.24 (95% CI, 2.24-8.04; P < .001), and ECMO versus off-pump odds ratio, 2.24 (95% CI, 1.38-3.65; P = .001). - Conclusions - Venoarterial ECMO is increasingly used at high-volume centers to support complex transplant recipients during double-lung transplantation. This practice is associated with more risk of PGD3 than off-pump transplantation but less risk than CPB. When extracorporeal life support is required during lung transplantation, ECMO may be the preferable approach when feasible.
Online verfügbar 4 Februar 2022, Artikelversion 14 Oktober 2022
Gesehen am 23.03.2023